The art of forgery : the minds, motives and methods of master forgers - Charney, Noah (Phaidon, 2015)
The Art of Forgery: Case Studies in Deception explores the stories, dramas and human intrigues surrounding the world's most famous forgeries - investigating the motivations of the artists and criminals who have faked great works of art, and in doing so conned the public and the art establishment alike